The Profile of 21st Century Skills on Students with Diverse Learning Preferences in EFL Classroom - Ismail Manangkari; Ernitasari Mulyadi; Abdah Abdah; Dewi Rara Amiati; Nurul Khasanah (Tadulako University, 2025)
This study aimed to investigate the profile of 21st-century skills among students with diverse learning preferences in an EFL classroom and to identify learning patterns associated with different learning preference groups. This study employed a qualitative descriptive design involving 17 students enrolled. Data were collected through classroom observations and semi-structured interviews conducted over the course of the study. Classroom observations focused on students’ participation, interactions, problem-solving behaviors, communication practices, and creative contributions during learning activities. The interviews were conducted to gain deeper insights into students’ learning experiences, preferred learning strategies, and perceptions of their own skill development. To ensure the credibility and trustworthiness of the findings, data were analyzed using triangulation techniques by comparing and cross-checking information obtained from observations and interview responses. The findings revealed that all participants demonstrated evidence of the four dimensions of 21st-century skills; however, the degree and manner in which these skills were expressed varied according to students’ learning preferences. Visual learners predominantly demonstrated creativity through visual representation, innovative project development, and the use of diagrams, images, and multimedia tools to convey ideas. Auditory learners exhibited stronger communication skills, characterized by active participation in classroom discussions, effective verbal interactions, and confidence in expressing opinions and responding to peers. Read/write learners showed higher levels of critical thinking through analytical reading, reflective writing, information synthesis, and the evaluation of arguments and evidence. Meanwhile, kinesthetic learners displayed stronger collaboration skills through active engagement in experiential learning tasks, group projects, and hands-on activities that required teamwork and collective problem-solving.